Hubungan Pembelajaran Pendidikan Agama Islam dengan Pembentukan Akhlak Siswa Kelas V SD Negeri Cijahe Curug Bogor - Marnianti Nervinarsya; Oking Setia Priyatna; Hasan Basri Tanjung (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
In learning Islamic religious education, it is not only taught about the obligation of a Muslim to worship, but in Islamic religious education learning is taught by educators about how to have good morals, how to speak well and politely to anyone, how to have good ethics, and in learning religious education. Islam is taught about matters relating to fellow human beings. Therefore, it is very important to create coaching and moral formation, especially at elementary school age, which is at that age the peak of the personality of students who are very vulnerable to things that are not good from the environment. Through learning Islamic religious education is expected to be able to improve and shape the morals of students for the better. The purpose of this study was to determine the learning of Islamic religious education and the moral formation of fifth grade students at SD Negeri Cijahe Curug Bogor and to find out whether there is a relationship between learning Islamic religious education and the moral formation of fifth grade students at SD Negeri Cijahe Curug Bogor. This study uses a quantitative approach with survey techniques. The results of this study are Islamic religious education learning for class V SD Negeri Cijahe Curug Bogor in the good category. This is based on the number of respondents' answers with the answer